2022
DOI: 10.1021/acsami.2c08572
|View full text |Cite
|
Sign up to set email alerts
|

Synergies of Atomically Dispersed Mn/Fe Single Atoms and Fe Nanoparticles on N-Doped Carbon toward High-Activity Eletrocatalysis for Oxygen Reduction

Abstract: PGM-free (platinum group metal) electrocatalysts are intensively investigated and used as low-cost catalysts for the oxygen reduction reaction (ORR) in the field of fuel cells, but further studying their performance improvement methods and actual reaction mechanism is still a big a challenge. In this work, a novel eletrocatalyst containing atomically dispersed Mn/Fe single atoms (SAs) and Fe nanoparticles (NPs) on N-doped carbonaceous (nanosheet/nanotube hybrids) is fabricated via a simple pyrolysis method. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 44 publications
0
17
1
Order By: Relevance
“…To uncover the influence of Mn, Fe, and the synergy Mn and Fe on de-NO x performance, the partial density of states (PDOS) of different optimized geometry structures was analyzed in detail (Figures –). By comparing the PDOS of T1, T2, and T3, it is found that the synergistic of Mn and Fe made the PDOS peaks of Mn–Mn and Fe–Fe shift positively (Figure a and b), which endows Mn–Fe–BTC with enhanced surface molecular adsorption capacity . At the same time, the PDOS of the catalyst active sites and the adsorbate elements connected to active sites in adsorption configurations (Figure ) were investigated.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…To uncover the influence of Mn, Fe, and the synergy Mn and Fe on de-NO x performance, the partial density of states (PDOS) of different optimized geometry structures was analyzed in detail (Figures –). By comparing the PDOS of T1, T2, and T3, it is found that the synergistic of Mn and Fe made the PDOS peaks of Mn–Mn and Fe–Fe shift positively (Figure a and b), which endows Mn–Fe–BTC with enhanced surface molecular adsorption capacity . At the same time, the PDOS of the catalyst active sites and the adsorbate elements connected to active sites in adsorption configurations (Figure ) were investigated.…”
Section: Resultsmentioning
confidence: 98%
“…By comparing the PDOS of T1, T2, and T3, it is found that the synergistic of Mn and Fe made the PDOS peaks of Mn−Mn and Fe−Fe shift positively (Figure 8a and b), which endows Mn−Fe−BTC with enhanced surface molecular adsorption capacity. 67 At the same time, the PDOS of the catalyst active sites and the adsorbate elements connected to active sites in adsorption configurations (Figure 7) were investigated. For NH 3 adsorption (Figure 9), d-sp hybridization occurred between N and Mn elements (Figure 9a, c, e, and g), which can establish a channel for electron transport between NH 3 and the active sites, enhance the transfer of charges, and promote further diffusion and reaction of NH 3 .…”
Section: In Situ Drift Analysis For De-nomentioning
confidence: 99%
“…Co 2 P/Co-NC had a d-band center of −2.06 eV, which was 0.41 eV lower than that of Co-NC (−1.65 eV). The downshift of the d-band center of Co 2 P/Co-NC means reduced binding between the oxygen species and the catalyst, which optimized the rate-determining step. ,, Therefore, the presence of Co 2 P effectively regulated the electronic structure of the Co–N 4 centers. Combined with XPS analysis results, it could be concluded that the electrons transferred from the Co–N 4 center to the peripheral carbon matrix due to the adjacent Co 2 P nanoparticle, which would regulate the density distribution of states in the Co–N 4 center. , The possible ORR mechanism is summarized in Figure S13.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the proposed solutions focus on lowering the PGM content by using Pt alloys or eliminating Pt by completely replacing it with other, more abundant metals, mostly PGM‐free that consist of first‐row transition metals 12 . These catalysts are either NPs or atomically dispersed metal sites, usually transition metal–nitrogen–carbon (M–N–C) sites 13–20 . So far, it has been difficult to find PGM‐free ORR catalysts without paying a high penalty in activity and/or durability 21–25 …”
Section: Introductionmentioning
confidence: 99%
“…12 These catalysts are either NPs or atomically dispersed metal sites, usually transition metal-nitrogencarbon (M-N-C) sites. [13][14][15][16][17][18][19][20] So far, it has been difficult to find PGM-free ORR catalysts without paying a high penalty in activity and/or durability. [21][22][23][24][25] Catalysts' supports also play an important role in the ORR catalytic activity and durability through surface interactions.…”
Section: Introductionmentioning
confidence: 99%